Peningkatan Kualitas Pelayanan Publik Melalui Citizen's Charter - Meirinawati Meirinawati; Indah Prabawati (Centre for Public Policy and Management Studies, 2015)
Public service is an effort to meet the basic needs for goods, services and administrative services provided by public service providers to the public. Good public services must be able to meet the needs of the community that are not convoluted, with a waiting time is relatively quick, and can be beneficial to all parties. It is claimed that poor public services are still becoming the reality of our current society. One of the efforts to encourage the government to improve the quality of public services is by using citizen's charter. It includes an agreement between service providers and service users about the types, procedures, costs, time and manner of service delivery according to service standards that are agreed by all parties involved.